Ischemic post-conditioning in acute ischemic stroke thrombectomy: A phase-I duration escalation study - Wu, Longfei; Zhang, Bohao; Zhao, Wenbo; Ji, Xunming; Wei, Ming (Frontiers in Neuroscience, 2022)
Background: Previous experimental studies have found that ischemic post-conditioning exhibits neuroprotective effects by alleviating ischemia-reperfusion injury in an acute ischemic stroke model, and its efficacy is thought to be related to the duration of ischemic post-conditioning. However, ischemic post-conditioning has not been used in patients with acute ischemic stroke. This study aims to determine the safety, tolerability, and maximum tolerable duration of ischemic post-conditioning in patients with acute ischemic stroke receiving mechanical thrombectomy. Methods: Patients with acute ischemic stroke with unilateral middle cerebral artery M1 segment occlusion eligible for mechanical thrombectomy will be enrolled. We adopt a 3 + 3 dose-escalation design with a duration escalation schedule of 0, 1, 2, 3, 4, and 5 min × 4 cycles for the ischemic post-conditioning study. After successful reperfusion following mechanical thrombectomy, the balloon for ischemic post-conditioning will be inflated at the site proximal to the culprit lesion four times for 0 - 5 min with low-pressure (3 - 4 atmospheres) inflations, each separated by 0 - 5 min of reflow. We pre-defined the major responses (vessel perforation or rupture, reocclusion of the culprit vessel after ischemic post-conditioning, vessel dissection, severe vasospasm, ischemic post-conditioning related thrombotic events, and rupture of the balloon used for ischemic post-conditioning) as the stopping rules. Each patient will undergo a rigorous evaluation to determine the safety, tolerability, and maximum tolerable duration of ischemic post-conditioning. Discussion: This will be the first clinical study to ascertain the safety and tolerability of ischemic post-conditioning in patients with acute ischemic stroke receiving mechanical thrombectomy. The maximum tolerable duration obtained in this study will also serve as a starting point for future studies on the efficacy of ischemic post-conditioning. Trial registration: Clinicaltrials.gov identifier: NCT05153655.